2013
DOI: 10.1039/c3ra43348j
|View full text |Cite
|
Sign up to set email alerts
|

PPH dendrimers grafted on silica nanoparticles: surface chemistry, characterization, silver colloids hosting and antibacterial activity

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 10069To link to this article : dendrimers grafted on silica nanoparticles: surface chemistry, characterization, silver colloids hosting and antibacterial activity. (2013) RSC Advances, vol. 3 (n° 41).Any correspondance concerning this service should be sent to the repository adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…These changes demonstrated that the cross-linked structure was generated via a Schiff base condensation between the copolymer precursor and the OG cross-linker. 34,35 The FT-IR spectrum of the degradation product in Fig. 1e presents the bands at 1607 cm -1 and 1730 cm -1 which were attributed to the vibrations of the N-H bending and of the C=O stretching, respectively.…”
Section: Characterization Of P(ah-co-ahh) Precursors and Hydrogelsmentioning
confidence: 98%
“…These changes demonstrated that the cross-linked structure was generated via a Schiff base condensation between the copolymer precursor and the OG cross-linker. 34,35 The FT-IR spectrum of the degradation product in Fig. 1e presents the bands at 1607 cm -1 and 1730 cm -1 which were attributed to the vibrations of the N-H bending and of the C=O stretching, respectively.…”
Section: Characterization Of P(ah-co-ahh) Precursors and Hydrogelsmentioning
confidence: 98%
“…Turrin and coworkers binded PPH to aminofunctionalized silica nanospheres through its aldehyde groups. The unreacted aldehydes of grafted PPH were then reacted with amine terminated poly(ethyleneglycol) (PEG).…”
Section: Silica Spheres For Dendrimer Functionalizingmentioning
confidence: 99%
“…The unreacted aldehydes of grafted PPH were then reacted with amine terminated poly(ethyleneglycol) (PEG). This hybrid material was incorporated for silver and silver oxide nanoparticles syntheses (Scheme ) …”
Section: Silica Spheres For Dendrimer Functionalizingmentioning
confidence: 99%
“…Therefore, some of these PPH dendrimers having phosphonic acids or phosphonates on their surface could undoubtedly stand as exciting candidates for the development of innovative therapeutic strategies for the treatment of chronic inflammatory diseases by targeting human monocytes . They have also shown promising abilities for natural killer cells expansion and anticancer cellular therapies thereby, and their implementation into functional nanomaterials is being studied …”
Section: Introductionmentioning
confidence: 99%